The Effect of Percutaneous Laser Disc Decompression on Reducing Pain and Disability in Patients With Lumbar Disc Herniation - Momenzadeh, Sirous; Koosha, Alireza; Kazempoor Monfared, Morteza; Bairami, Jafar; Zali, Alireza; Ommi, Davood; Hosseini, Behnam; Hashemi, Masoud; Sayadi, Shahram; Aryani, Reza; et al. (Journal of Lasers in Medical Sciences, 2018)
Introduction: As low back pain incidence is increasing, noninvasive modalities are gaining attention for their ability to achieve the best possible outcome with the least complications. Percutaneous laser disc decompression (PLDD) is currently popular for this purpose. This study aims to evaluate the effect of PLDD on disability and pain reduction in patients with lumbar disc herniation. Methods: Thirty patients were enrolled in this study. Spinal nerve blocks were conducted by laser discectomy single stage injection of a needle into the disc space. The nucleus pulposus of herniated discs were irradiated with laser in order to vaporize a small part of the nucleus pulposus of the intervertebral discs and reduce the voluminosity of diseased discs. Patients were treated with 1000 J of 980 nm diode laser with 5 W energy. In order to measure the severity of pain, visual analog scale (VAS) and also ODI (Oswestry Disability Index) were used. Data were analyzed using SPSS version 12. Results: Thirty patients participated in this trial including 11 men and 19 women with a mean age (SD) of 40.8 (10.8) years. The mean patients VAS score and ODI level before and after discectomy showed statistically significant differences. The mean VAS and ODI scores showed no statistical difference between males and females (P < 0.05) and percutaneous laser discectomy decreased the VAS and ODI at both groups of patients similarly. Conclusion: We found the use of PLDD reduces pain and disability in patients as a noninvasive procedure.